Parallel time-delay estimation algorithm for GMSK mixing signals - RUI Guo-sheng1; XU Bin2; ZHANG Song2 (Tongxin xuebao)
Parallel time-delay estimation algorithm was proposed for GMSK mixing signals based on linear approxima-tion approach.Parallel estimation equations were built in flat-fading channel according to autocorrelation of over-sampling based mixing signals and then Cramer-Rao bound for parallel time-delay estimation was deduced.Poly-nomial fitting method was uesed to simplifying nonlinear complexity of GMSK shaping filter and estimation equations were resolved numerically by gradient descent algorithm with fast convergence.Simulation results show that its estimat-ing performance is good and the variance of estimation error is close to Cramer-Rao bound.As a non-preamble aided al-gorithm with lower complexity it is significant for the next blind processing.